The Movement of Praxis in the Constitution of a Conception of Modeling in Mathematics Education - Malheiros, Ana Paula dos Santos [UNESP] (FapUNIFESP (SciELO), 2024)
Considering the thematic section of Bolema, in celebration of the 40th anniversary of the Graduate Program in Mathematics Education at Unesp Rio Claro, this article aims to understand the movement of practice in the constitution of a concept of modeling of a graduate student, throughout their academic career. It is a theoretical study based on the qualitative paradigm. It discusses how praxis, as well as other concepts from Paulo Freire's legacy, have been part of a journey of research, teaching, and practice, helping to give new meaning to a conception of modeling based on articulations between theory and practice, action and reflection, objectivity and subjectivity. In describing and problematizing these changes, an oppressive reality in the schools of basic education is denounced. This reality aims to castrate curiosity and standardize education in search of indices that favor the maintenance of the status quo, which can be identified as a limiting situation, in order to announce, in a hopeful way, the possibilities of working with modeling, the unprecedented ones that are feasible, based on its articulation with the existing teaching materials that are veiledly compulsory in these schools. And this hope, which is action, is made in practice
O Movimento de Práxis na Constituição de uma Concepção de Modelagem em Educação Matemática
Keywords: Denunciation and proclamation; Mathematical Modeling; Paulo Freire; Schools; To be more